2011
DOI: 10.2174/156720111796642345
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Membrane Capsules of Phenylephrine Hydrochloride: An Osmotically Controlled Drug Delivery System

Abstract: The aim of the current study was to develop osmotically controlled release system of freely water soluble drug phenylephrine hydrochloride by use of asymmetric membrane capsules to reduce the dosing frequency and consequently improve the patient compliance. Ethyl cellulose asymmetric membrane capsules were developed by phase inversion process and solubility modulation was accomplished by common ion effect wherein sodium chloride was included in the formulation that also served as an osmogen. The effect of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results concluded that, when osmogen and pore former were at high levels in FAMC6 and FAMC8, higher release (average release,~92%) was observed than FAMC1 and FAMC2 (average release,~85%), having lower levels of both variables. The effect is attributable to the combined result of increased perforation of the capsular wall and osmotic gradient that has been documented in our previous studies (8)(9)(10)(11). Fig.…”
Section: In Vitro Drug Releasesupporting
confidence: 56%
See 2 more Smart Citations
“…The results concluded that, when osmogen and pore former were at high levels in FAMC6 and FAMC8, higher release (average release,~92%) was observed than FAMC1 and FAMC2 (average release,~85%), having lower levels of both variables. The effect is attributable to the combined result of increased perforation of the capsular wall and osmotic gradient that has been documented in our previous studies (8)(9)(10)(11). Fig.…”
Section: In Vitro Drug Releasesupporting
confidence: 56%
“…Hence, a solubility modulator (coated NaCl) was used. This approach (based on the common ion effect) has been utilized by us in the development of AMCs of highly water-soluble drugs-phenylephrine hydrochloride (10) and triprolidine hydrochloride (11).…”
Section: Equilibrium Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results are consistent with the literature report on acyclovir as “slightly soluble in water” at room temperature (22–25°C) and solubility values range from 1.2 to 1.6 mg/mL [ 17 , 18 ]. The solubility is a prominent factor in governing the drug release from an osmotically controlled drug delivery system [ 19 ]. A poorly soluble drug (<10 mg/mL) will be governed by first-order release kinetics rather than zero-order kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Based on Ridgway [ 20 ], the size of a capsule is classified into five different classes, with size 00 as the biggest and size 3 as the smallest. Kumar et al [ 35 ] developed an osmotically controlled release system of phenylephrine hydrochloride in an ethyl cellulose capsule. Their results showed that the lengths of the cap and body of the capsule were 10.45 ± 0.34 mm and 17.42 ± 0.22 mm, respectively.…”
Section: Hard Capsules: Preparation and Characterisationmentioning
confidence: 99%